Modeling of Meteorological Parameters for Libya - Sh-Eldin, Mohammed Ali (2003)
Libya is a developing country with large natural resources. The surface of Libya amounts to 1,775,500 km2 and is the fourth biggest African country. The population of Libya amounts to approximately 5 million and is concentrated on the coastal strips though it is divided among cities, villages, and rural areas, while the desert has some green, sunny, and windy oasis where many tribes live there. Due to the random distribution of the villages and oasis among the vast Libyan area it will be very expensive to provide these remote areas with electric energy from the country's grid of electricity. This reason encourages us to consider renewable energy options such as solar, wind, as alternatives. For successful energy research and applications, weather parameters of Libya (wind speed, sunshine duration, humidity, temperature, rainfall, and global solar radiation) have to be modeled. For solar energy applications, information on global solar radiation for specific sites that have no records of weather data is required. A model based on Angstrom formula using weather data such as sunshine, temperature and humidity of five stations in Libya is described. The criteria of choosing the best formula among all formulae were based on R2 value (coefficient of determination), and the value of modeling efficiency (EFF). We can accept any of equations 2.12,2.19, and 2.20 to predict global solar radiation especially the nonlinear equation 2.20.